Empowerment of Gunung Sari Village Community Groups, to optimize the potential of the village towards the Tourism Independent Village - Prihastuti Harsani (Research Collaboration Community (RCC), 2020)
The tourism sector in Gunung Sari Village, Pamijahan District, Bogor Regency, is not the main sector in its community activities. The existence of natural tourism in the form of waterfalls, camping ground and hot springs is a potential for the village to realize the Bogor Regency Mission. Existing tour operators are not residents or village communities. The active participation of village communities has not been seen in the management, operational and maintenance of tourist attractions. The tour paramilitary group 20 can be an agent for villages to empower communities in the tourism sector. Srikandi Gunung Sari group is a community group that involves mothers and produces local food products in the form of banana chips and cassava. In an effort to increase the active participation of village communities in tourism activities in Gunung Sari Village, the empowerment of the Laskar Tourism Group 20 and Srikandi Gunung Sari was carried out through education, workshops, mentoring and facilitation activities. The main target of this activity is the village community who can independently manage, maintain and improve the tourism sector in Gunung Sari village towards a sustainable tourism independent village.